Limnoecology and carp fish species peak spawning timing in haor basin of Bangladesh - Ahmad, Md. Foysal; Kabir, Muhammad Anamul; Zulhisyam Abdul Kari; Alam, Md. Tariqul; Lee, Seong Wei (Penerbit Universiti Kebangsaan Malaysia, 2019)
The present study was conducted to investigate the peak spawning timing based on the reproductive performance of carps species related to limnoecology variables, emphasizing to assess within fish population breeding variability and monthly effects over a period from April to July 2016 in the haors basin of Bangladesh. The reproductive performances were evaluated through artificial breeding technique by hormone injection in matured brood fish. The reproductive performance in terms of mean fecundity, egg weight, fertilization, hatchling and larval survival were significantly (P<0.05) highest in the month of May to June, and April compared to the months of spawning timing for the three Indian major carps, and the three exotic carp respectively. The ovulation and hatching time were significantly (p<0.05) highest in the month of July and April for the Labeo rohita, in the month of Aril for Catla catla and Cirrhinus cirrhosus and for the three exotic carp in the month of June to July compared with the others months of the breeding season. However, total length, weight and spawning response were not significantly (P>0.05) different among the months of the breeding time for the six carp species and a trend similar to the spawning success was also observed and numerically the mean value of the spawning response rate was between 88 to 93% and 83 to 90% for the three Indian major carps and the three exotic carp respectively among the months of the study. Furthermore, mean monthly values of limnoecological variables such as temperature, pH, and dissolved oxygen were not significantly (P>0.05) different among the months of the breeding season of the carp species in the three haor study sites. This study may serve as an update on carp fish species peak spawning timing related to limnoecological variables in the haor basin for carps species broodstock sustainable management to get quality seeds in the aquaculture hatchery industry.